Risk Cycles, Capitalism and the Future of Work - Peetz, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
AbstractThis paper interprets extensive empirical data on the growth and then stagnation of “modes of flexibility” by using labour process theory, specifically with respect to control and resistance. In a “risk cycle,” management initially seizes an opportunity to reduce costs by transferring risk from capital to labour through some mode of flexibility. The chosen mode is used more and more until further expansion is blocked by the need to overcome resistance, to obtain consent and/or to exercise control. Management then seeks a new mode. The risk cycle is consistent with OECD data on “temporary employment,” and Australian data on “casual employment.” Implications for the gig economy and the future of work are discussed.SummaryTo understand the future of work, we need to integrate two aspects of industrial relations theory and research: 1) the extensive empirical investigations into the growth of job precarity; and 2) the role of control and resistance in labour process theory.Central to such integration is the “risk cycle.” In a risk cycle, management initially seizes an opportunity to reduce costs by transferring risk from capital to labour through some “mode of flexibility.” The chosen mode is used more and more until further expansion is blocked by the need to overcome resistance, to obtain consent and/or to exercise control. While the urge to transfer risk and reduce costs is ever present, management’s success waxes and wanes. As each mode reaches its limit, management seeks a new mode, which may be a modernized version of an old one.This article examines cross-national trends in temporary employment. In the OECD data, the temporary employment rate does not inexorably rise. Instead, in most countries, it peaks and then falls, or exhibits some other more complex pattern. In the majority of OECD countries, it peaked well before the late 2010s, with the highest level being most commonly reached in 2011. The patterns of risk cycles vary between industries and firms, reflecting the specific circumstances of each situation.In Australia, another measure, casual employment, rose during the 1980s and 1990s, and plateaued from the early 2000s. Casualization has followed quite different trajectories for full-time and part-time workers, a reflection of employer practices in different industries.The future of work can be analyzed through this lens. The app-based gig economy has reduced costs for corporations, with many people being defined as contractors, and greater app-enabled control. However, it is meeting with resistance from workers and the state, and the control problem has not been fully overcome. While app technology may shift the frontier of control, it is unlikely that contracting could ever come to dominate the employment relationship.